A new real-time monitoring technique in calculation of the p-y curve of single thin steel piles considering the influence of driven energy and using strain gauge sensors - Moayedi, Hossein; Nazir, Ramli; Gor, Mesut; Kassim, Khairul Anuar; Foong, Loke Kok (Elsevier Sci Ltd, 2020)
This paper presents the modelling of a single thin steel pile to simulate the relationship between soil pressure reaction (p) and lateral deflection (y). The presented simulation helps to produce a more reliable p-y curve graph using skin-based strain sensors. Therefore, the main objective of this study is to evaluate the p-y curve obtained from physical modelling in order to calculate the subgrade reaction modulus (Ks) and maximum bending moment in both loose and dense soil conditions using differentiation and integration methods. In this regard, extensive instrumentation and unique data acquisition system was used around the single thin steel pile, where the results provided the most reliable graph of the moment (M) versus depth (z) from the soil surface. In addition, the effect of pile driving energy with respect to the different relative densities of soil is obtained. The results indicated that as the density of sand increases, the subgrade modulus and maximum bending moment of the pile increases. The increases in passive soil pressure could cause significant decreases in pile lateral deflection. Furthermore, the p-y behaviour of the single thin pile is hardly affected by the installation of derivation energy. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Strain gauge sensors; Pile monitoring; Driven energy; Thin piles; Lateral loading